O complexo religioso e os batistérios de Mértola na Antiguidade Tardia - Virgílio Lopes (Medievalista)
The theme of the present work is part of an archaeological research that I have been developing since 1990 in Mértola’s Archaeological Centre. The results are the outcome of several archaeological excavation I have carried out as co-responsible, integrated into the institution’s team, and that has greatly contributed, on a continuous basis, to the knowledge of the material culture and historical topography of the city of Myrtilis city and its territory in Late Antiquity.